Kako pomenja pesem - Balžalorsky, Varja (Primerjalna književnost, 2016)
The theoretical part of this article briefly outlines the shifts in the conceptualization of signifiance in poetic language, as they rudimentary appear in the work of Émile Benveniste and acquire the form of a firm theoretical platform in Henri Meschonnic's poetics of discourse. The second part features a case study of the poem "La Ralentie" (Woman in Slow Motion) by Henri Michaux in order to demonstrate how the concepts discussed function in the practical study of poetry.
Keywords: Benveniste, Émile, 1902-1976; Meschonnic, Henri, 1932-2009; Michaux, Henri, 1899-1984; poezija; pesniški jezik; pesniška govorica; meaning; pomen; ikoničnost; ritem; semantična prozodija; pesemski subjekt; francoska poezija